Chukotka Peninsula counts and estimates of the number of migrating bowhead whales (Balaena mysticetus) - Melnikov, Vladimir V.; Zeh, Judith E. (J. Cetacean Res. Manage., 2023)
In May and June 2000-01, shore-based counts of migrating bowhead whales (Balaena mysticetus) were conducted from Cape Pe’ek on the Chukotka Peninsula, Russia. These counts, designed to permit estimation of the number of whales migrating past Cape Pe’ek from midMay to mid-June, were similar to those of bowhead whales migrating past Barrow, Alaska and of gray whales migrating past Granite Canyon, near Monterey, California, except that no experiments designed for estimating detection probabilities P were conducted at Cape Pe’ek. Under the assumption that P=1 (all whales passing during watch with acceptable visibility conditions were seen), the estimated number of migrating bowheads was 430 (CV 22%) in 2000 and 558 (CV 31%) in 2001. The weighted geometric mean of these estimates is 470 with 95% confidence interval 332-665. If P was assumed to be similar to the detection probabilities estimated from the Barrow bowhead count or the Granite Canyon gray whale count, the weighted geometric mean estimate was approximately twice as large. Of at least 94 bowhead whales seen from Cape Pe’ek in June of 2001, at most one could have been among those counted by the survey near Barrow that year.